Respuesta :

Answer:

You can prove this statement as follows:

Step-by-step explanation:

An odd integer is a number of the form [tex]2k+1[/tex] where [tex]k\in \mathbb{Z}[/tex]. Consider the following cases.

Case 1. If [tex]k[/tex] is even we have: [tex](2k+1)^{2}=(2(2s)+1)^{2}=(4s+1)^{2}=16s^2+8s+1=8(2s^2+s)+1[/tex].

If we denote by [tex]m=2s^2+2[/tex] we have that [tex](2k+1)^{2}=8m+1[/tex].

Case 2. if [tex]k[/tex] is odd we have: [tex](2k+1)^{2}=(2(2s+1)+1)^{2}=(4s+3)^{2}=16s^2+24s+9=16s^{2}+24s+8+1=8(2s^{2}+3s+1)+1[/tex].

If we denote by [tex]m=2s^{2}+24s+1[/tex] we have that [tex](2k+1)^{2}=8m+1[/tex]

This result says that the remainder when we divide the square of any odd integer by 8 is 1.

ACCESS MORE